2017
DOI: 10.1111/jeu.12427
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cryptic Diversity and Distribution Patterns in the Mallomonas kalinae/rasilis Species Complex with a Description of a New Taxon—Mallomonas furtiva sp. nov.

Abstract: A complex of closely related Mallomonas taxa belonging to the section Papillosae, M. kalinaeRez a cov a and M. rasilis D€ urrschmidt, has been studied in detail by molecular and morphometric methods. Our investigations uncovered the existence of a new species found in water bodies in Vietnam, which we describe here as Mallomonas furtiva sp. nov. This taxon is morphologically very similar to M. kalinae, from which it differs by minute, but statistically significant morphological differences on the structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Examples include taxa such as Mallomonas spinosa [79], M. fimbriata [81], M. pseudobronchartiana [86], and M. lusca [116]. Analysis of images illustrated earlier under the epithets of other species ("deviating" morphotypes or misidentified taxa) from different regions of the world [41,58,60,100] have helped clarify the distribution features of some recently described taxa, such as Mallomonas cattiensis [84], M. neoampla [82], M. furtiva [87], M. loricata [77], and M. siderea [78].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples include taxa such as Mallomonas spinosa [79], M. fimbriata [81], M. pseudobronchartiana [86], and M. lusca [116]. Analysis of images illustrated earlier under the epithets of other species ("deviating" morphotypes or misidentified taxa) from different regions of the world [41,58,60,100] have helped clarify the distribution features of some recently described taxa, such as Mallomonas cattiensis [84], M. neoampla [82], M. furtiva [87], M. loricata [77], and M. siderea [78].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of cryptic/pseudo-cryptic species have been found-for example, in the M. furtiva/M. kalinae Rezácova [87] and S. curtispina/S. longitubularis [114] complexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have revealed a very rich flora from the order Synurales, including 57 taxa from genera Mallomonas and Synura. Indeed, 19 new species from the genus Mallomonas [40,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] and one Synura species [60] were described in these studies. However, the northern part of Vietnam, which differs in hydrology, climate, and anthropogenic impact from the Central and Southern provinces, is lacking sufficient descriptive studies.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive studies of the last decade with molecular and morphological approaches show that the real diversity of the genus is underestimated. Over last ten years, twenty new Mallomonas species have been described from different regions in Asia, including one from Russia (Gusev & Kulikovskiy 2013), two from China (Ma & Wei 2013;Němcová et al 2015), six from Korea (Kim & Kim 2008;Kim & Kim 2010;Jo et al 2013;Kim et al 2014), and eleven from Vietnam (Gusev 2012(Gusev , 2013(Gusev , 2015aGusev et al 2015Gusev et al , 2016Gusev et al , 2018. Two of these, Mallomonas elevata Han Soon Kim Dürrschmidt, and M. liturata K.H.…”
Section: Introductionmentioning
confidence: 99%